2014
DOI: 10.1371/journal.pone.0086470
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptor 3 Interacts with and Activates TGFβ-Activated Kinase 1 Tyrosine Phosphorylation and NFκB Signaling in Multiple Myeloma and Bladder Cancer

Abstract: Cancer is a major public health problem worldwide. In the United States alone, 1 in 4 deaths is due to cancer and for 2013 a total of 1,660,290 new cancer cases and 580,350 cancer-related deaths are projected. Comprehensive profiling of multiple cancer genomes has revealed a highly complex genetic landscape in which a large number of altered genes, varying from tumor to tumor, impact core biological pathways and processes. This has implications for therapeutic targeting of signaling networks in the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 84 publications
0
24
0
Order By: Relevance
“…Upon activation, TAK1 phosphorylates IKK␣/␤, thereby activating the canonic NF-B pathway. Whether TAK1 is required for the FGF pathway to cross-talk with NF-B is not fully clear, although one report found that FGFR interacts with TAK1 in multiple myeloma and bladder cancer cells (23). To determine whether the FGF pathway enhanced NF-B signaling via activation of TAK1, MEFs were treated with the TAK1 inhibitor, (5Z)-7-oxozeaenol.…”
Section: Tak1 Is Required For Fgfr1 To Augment Nf-b Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon activation, TAK1 phosphorylates IKK␣/␤, thereby activating the canonic NF-B pathway. Whether TAK1 is required for the FGF pathway to cross-talk with NF-B is not fully clear, although one report found that FGFR interacts with TAK1 in multiple myeloma and bladder cancer cells (23). To determine whether the FGF pathway enhanced NF-B signaling via activation of TAK1, MEFs were treated with the TAK1 inhibitor, (5Z)-7-oxozeaenol.…”
Section: Tak1 Is Required For Fgfr1 To Augment Nf-b Signalingmentioning
confidence: 99%
“…In addition, the cross-talk between the FGF and NF-B signaling pathways remains controversial. In some reports, FGF signaling positively regulates the NF-B pathway (23)(24)(25)(26)(27)(28)(29), whereas in others, FGF signaling negatively regulates the NF-B pathway (30 -32). In addition, the mechanism by which FGFR regulates the NF-B pathway is unclear, although downstream signaling pathways of FGFR kinases, such as the extracellular signal-regulated protein kinases (ERKs), phosphatidylinositol 3-kinase (PI3K)/AKT, or phospholipase C (PLC)-␥ pathways, are known to promote activation of the NF-B pathway.…”
mentioning
confidence: 99%
“…We have earlier reported that transient FGF stimulation results in a sustained activation of NFkB signaling, which is critical for FGF memory establishment (Poole et al, 2014). IL1a (Niu et al, 2004;Melisi et al, 2009) and FGF (Muddasani et al, 2007;Salazar et al, 2014) have been demonstrated to activate the proinflammatory NFkB pathway. Moreover, IL1a expression and NFkB signaling constitute an autoregulatory feedback loop that maintains IL1a production (Niu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in growth factors, cell signaling genes, DNA repair, cell cycle and apoptosis genes have been deeply investigated for their role in the genetic susceptibility to MM. It was demonstrated that the activation of the nuclear TF nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) seems to be involved in the enhancement of cell proliferation in MM pathogenesis [97], while the IκBα (rs2233406, rs3138054, rs2233419), an inhibitor of NF-κB pathway and the transcriptional activator TRAF3 (rs12147254) have been associated with a protective effect on MM development [98]. As regard to polymorphisms related to insulin metabolism, the IGF1 genes (rs7965399, rs2195239, rs2373722) and the IGFBP3 (rs3110697), and two in the IRS1 gene were associated with increased or decreased MM risk.…”
Section: Pharmacogenomics In Mm: a General Viewmentioning
confidence: 99%
“…Moreover, SNPs in BAX, CASP3 and CASP9 genes were found to be associated with MM risk and could have an important role in its etiology as well as SNPs in XRCC3 and ERCC2 genes, while no association was found for the GSTM1, GSTT1 and GSTP1 of the glutathione-S-transferase gene and the variant codon 72 p53 allele. The potential role in genetic susceptibility to MM was investigated also for SNPs in adsorption distribution metabolism and excretion genes, but with modest evidence of association with MM risk [92,97]. Scientific data demonstrated an association with an increased MM risk in the GSTT1 null genotype, the homozygote genotype in the rs662 in the PON-1 genes and NAT2 rapid/slow phenotype [93], while polymorphisms in genes involved in benzene metabolism were associated to an increased susceptibility to MM for carriers of 'high-risk genotypes/phenotypes' of GSTT1 (null), NQO1 (187PS/SS, rs1800566), mEH (high activity) and for the mEH H139R (rs2234922) genes polymorphism [103].…”
Section: Pharmacogenomics In Mm: a General Viewmentioning
confidence: 99%